Ethiopia: Natural Resource Exploitation and Emerging Investors - Besada, Hany (Revue Gouvernance / Governance Review)

(untitled) (Centre d’études en gouvernance de l’Université d’Ottawa, 2017)
Natural resource governance accelerates development. Ethiopia, a low-income country, passed land legislation in the 1990s and subsequently exhibited exceptional economic growth and human development improvements. From 2004 to 2014, Ethiopia’s average annual GDP growth rate was about nine per cent. Nevertheless, over 80% of the population remain food insecure. Using a literature review and interviews, this case study examines Ethiopia’s economic and social development through a land governance lens. It aims to document the flaws in Ethiopia’s regulatory framework that hinder vulnerable communities from leveraging the benefits of greater foreign direct investments (FDI) and resultant economic growth. The case analyzes Ethiopia’s agricultural governance framework and the impact of FDI-driven large-scale farming on smallholder communities, and concludes with suggestions for alternative investment approaches. The case study reveals that Ethiopian government legislation and resultant macroeconomic growth has yet to deliver inclusive and stable economic gains for many of the vulnerable smallholder communities. There is a need to advance further regulation and policies that not only protect these vulnerable communities, but also enhance economic and trade incentives for potential foreign investors.